2015
DOI: 10.1007/s13197-015-1931-z
|View full text |Cite
|
Sign up to set email alerts
|

A high correlation indicating for an evaluation of antioxidant activity and total phenolics content of various chilli varieties

Abstract: Use of dimethyl sulfoxide (DMSO) as a suitable extraction solvent under the optimum conditions of microwave assisted extraction (MAE) prior to total phenolics determination and antioxidant activity assay was conducted. The MAE method was done with 0.05 g sample in 10 mL DMSO at 500 W within 5 min. The effects of DMSO on various antioxidant activities using DPPH(·+), DMPD(·+), ABTS(·+) and FRAP, and Folin-Ciocalteu reagent were investigated. From the results, it is clearly demonstrated that the DMSO itself show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Polyurethane carrier used for chili pepper extract solubilized in 10 mL solvent (70% ethanol) and was heated in a microwave-assisted extraction (500 W for 5 minutes) according to a procedure described in the literature. 19,20 The extract was cooled and centrifuged at 4,000 rpm for 10 minutes.…”
mentioning
confidence: 99%
“…Polyurethane carrier used for chili pepper extract solubilized in 10 mL solvent (70% ethanol) and was heated in a microwave-assisted extraction (500 W for 5 minutes) according to a procedure described in the literature. 19,20 The extract was cooled and centrifuged at 4,000 rpm for 10 minutes.…”
mentioning
confidence: 99%
“…The result of sample preparation is discussed and shown in Supporting Information, Fig. S3, S4, and Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these phytochemicals also possess antimicrobial, antiviral, anti‐inflammatory, anticarcinogenic and antidiabetic properties, as well as gastrointestinal benefits . These properties have been applied to the food, pharmaceutical and cosmetic industries; therefore, the demand for chili as a raw material has recently increased by ∼6% …”
Section: Introductionmentioning
confidence: 99%
“…[6] These properties have been applied to the food, pharmaceutical and cosmetic industries; therefore, the demand for chili as a raw material has recently increased by~6%. [7] Metabolites display accumulation patterns that generally depend on the environment and genotype, generating a wide sensorial variation within the genus. [8] Several studies have shown the pharmaceutical potential of Capsicum, particularly in commercial cultivars of Capsicum annuum L. [9] and in highly pungent genotypes of C. chinense JACQ.…”
Section: Introductionmentioning
confidence: 99%